Trace elements in soils and plants - Kabata-Pendias, Alina
The Anthroposphere.--Soils and soil processes.--Soil constituents.--Trace elements in plants.--Elements of group I.--Elements of group II.--Elements of group III.--Elements of group IV.--Elements of group V.--Elements of group VI.--Elements of group VII.--Elements of group VIII.